Removal of Pb2+, Cu2+ AND Cd2+ IONS from aqueous solution by carboxymethyl sago starch and carboxymethyl sago starch/chitosan hydrogels - Basri, Sri Norleha (2015)
Modified polysaccharides such as starch and cellulose play important role in the polymer research because they are from natural resources and biodegradable. The main objective of this study was to prepare the hydrogels from modified sago starch and chitosan which were then applied as metal scavenger for lead (Pb), copper (Cu) and cadmium (Cd). In this study, carboxymethyl sago starch (CMSS) and chitosan were dissolved in L (+)-lactic acid (LA) and cross-linked by using electron beam (EB) irradiation. The highest gel content of hydrogel was obtained from 60% (w/v) of CMSS in 0.6 M of LA at 20 kGy EB irradiation. Similar composition as CMSS hydrogel has been used for CMSS/chitosan (CMSS/Chi) hydrogel with the addition of 4% (w/v) of chitosan which showed high metal uptake. Then, both CMSS and CMSS/Chi hydrogels were structurally and morphologically characterized by Fourier Transform Infrared (FT-IR) and Scanning Electron Microscopy (SEM). The hydrogels (metal uptake. Meanwhile, the Pb ions uptake by both CMSS and CMSS/Chi hydrogels are quite similar due to high molecular weight and radius which caused less attraction towards nucleus and easily be bonded to active binding site of hydrogels. All the metal uptake achieved equilibrium within 1 hour reaction time and showed the pseudo second order reaction in kinetic study. Except the reaction between CMSS hydrogel and Pb ion, the isotherm study showed the reaction was followed the Freundlich isotherm model. In addition, under competitive condition, CMSS/Chi hydrogel showed high selectivity towards Pb ion compared to Cu and Cd ions. This probably due to small pore size of CMSS/Chi hydrogel as shown by SEM micrograph which have the ability to entrap the large Pb ions and hindered the active site from in contact with Cu and Cd ions. In conclusion, these results supported the role of both CMSS and CMSS/Chi hydrogels as metal scavenger for Pb, Cu and Cd ions.